RELATIONAL BENEFIT, KEPUASAN, DAN LOYALITAS PELANGGAN PADA BENGKEL PT HONDA DEWATA MOTOR - Prayoga, I Made Surya; Yasa, Ni Nyoman Kerti; Wardana, Made (Jurnal Manajemen dan Kewirausahaan, 2015)
Providing customer satisfaction consistently could make customers become loyal to the company. Loyal customers were the source of income and they would help the company to survive in the business competition. Relationship marketing was a strategy that can be used to achieve these goals, through relational benefits strategy. The company could give the benefit from relationship between companies and customers. This study analyzed relationship marketing in the workshop of PT Honda Dewata Motor through 153 respondents. The results show that confidence benefits and social benefits have positive effect on customer satisfaction. Special treatment benefits had no significant effect on customer satisfaction and loyalty to workshop. Customer satisfaction had positive impact to customer loyalty significantly.